Asynchronous Bilateral Renal Infarction and Thrombophilia With Associated Gene Mutations in a 43-Year-Old Man: A Case Report. Issue 14 (April 2016) - Zhou, Xu-Jie; Liu, Li-Jun; Chen, Min; Zhou, Fu-De
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Renal infarction (RI) is frequently misdiagnosed or diagnosed late because of its rarity and nonspecific clinical presentation, which may result in irreversible damage to the renal parenchyma or increase the risk of other embolic events affecting additional organs. Multiple causal mechanisms and cases of idiopathic RI have been reported, but the causal factors are not clear in most cases. Here, we report the case of a patient with heterochronic bilateral RI caused by thrombophilia. Although he had several risk factors for hypercoagulation disorders, two gene mutations— MTHFR 677 C>T and PLG 1858G>A—were identified by genome sequencing of the entire exome. The findings suggest the possibility of a synergistic relationship between the two gene mutations. Thus, screening for gene mutations may provide additional clues for clarifying the cause of RI and thrombophilia.